2017
DOI: 10.1016/j.radcr.2017.07.013
|View full text |Cite
|
Sign up to set email alerts
|

Fetal MRI diagnosis of 2 types of left pulmonary artery sling

Abstract: We report on 2 different types of left pulmonary artery sling (LPAS), types IA and IIB, diagnosed by fetal magnetic resonance imaging (MRI). We suggest that fetal MRI is an effective tool for accurately diagnosing LPAS and helping guide its perinatal management. Fetal MRI is relatively unaffected by the conditions that limit visualization by echocardiography. When prenatal ultrasound detects either a possible anomalous origin of the left pulmonary artery or a tracheobronchial anomaly, fetal MRI may provide add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…The prenatal features of 4 additional cases have been described retrospectively after a postnatal diagnosis of LPAS was made by MRI or CT imaging. 3,[5][6][7][8] Only three out of thirteen cases are isolated and have no cardiac and extra cardiac findings on fetal echocardiography examination. 3,[5][6][7][8] Only three out of thirteen cases are isolated and have no cardiac and extra cardiac findings on fetal echocardiography examination.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%
See 2 more Smart Citations
“…The prenatal features of 4 additional cases have been described retrospectively after a postnatal diagnosis of LPAS was made by MRI or CT imaging. 3,[5][6][7][8] Only three out of thirteen cases are isolated and have no cardiac and extra cardiac findings on fetal echocardiography examination. 3,[5][6][7][8] Only three out of thirteen cases are isolated and have no cardiac and extra cardiac findings on fetal echocardiography examination.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%
“…[6][7][8] In these previously reported cases, 7 out of 13 (% 54) had an abnormal cardiac axis, position, and/or echogenic lungs which resulted in further imaging before and after birth. 3,4,10 In 4 out of 13 cases (% 30), structural heart diseases have been reported. 3,4,10 In 4 out of 13 cases (% 30), structural heart diseases have been reported.…”
Section: Discussion and Con Clus I Onmentioning
confidence: 99%
See 1 more Smart Citation
“…The diagnostic role of fetal MRI, as a complementary second level tool useful when the ultrasound is hampered by inadequate acoustic window, has recently been proposed by several groups. 9,[38][39][40][41][42] In a prospective single-center study, a combination of SSFP and SS-T 2 -TSE sequences identified the same diagnosis as postnatal findings in 79% of fetuses with CHD at a mean gestational age of 25.5 weeks. 38 In that study the diagnostic sensitivity for cardiac anomalies by ultrasound screening performed by an obstetrician and by a fetal cardiac specialist were 46% and 82%, respectively.…”
Section: Complementary Diagnostic Role Of Fetal Cardiac Mrimentioning
confidence: 95%
“…However, it may be limited by fetal position, oligohydramnios, overlying bone, and obesity. The diagnostic role of fetal MRI, as a complementary second level tool useful when the ultrasound is hampered by inadequate acoustic window, has recently been proposed by several groups . In a prospective single‐center study, a combination of SSFP and SS‐T 2 ‐TSE sequences identified the same diagnosis as postnatal findings in 79% of fetuses with CHD at a mean gestational age of 25.5 weeks .…”
Section: Complementary Diagnostic Role Of Fetal Cardiac Mrimentioning
confidence: 99%